On the role of the librarian - Rodríguez Castro, Hernán (1995)
For many centuries the librarian had as a basic and primordial function the conservation and Custody of those treasures. As time went by, the characteristics of the libraries and therefore of the librarian activity changed "they gained a lot in their growth and development" demanding as a consequence that the librarian extend their custody and worry even more about their arrangement.